G protein-coupled receptors as promising targets in cancer. (February 2021) - Perez Almeria, Claudia V.; Setiawan, Irfan M.; Siderius, Marco; Smit, Martine J.
Abstract: G protein-coupled receptors (GPCRs) control diverse cellular functions, and their dysregulation is involved in a plethora of diseases including tumorigenesis. In the last decade, the association of GPCRs with cancer has become apparent and offers new opportunities to target GPCRs in oncology. GPCR overexpression and mutations lead to aberrant activation of pro-oncogenic pathways inducing tumor progression. In this review, we describe how GPCRs activate some main signaling pathways that contribute to different cancer hallmarks, including cell transformation, proliferative signaling, immune evasion, angiogenesis, and metastasis. Thereafter, we highlight different approaches to target GPCRs, including small molecules and biologics (e.g. monoclonal antibodies and nanobodies) and combinatorial (immuno)therapies that are emerging with promising effects for cancer treatment.